Reduction of insulin requirement in type 1 diabetes induced by BCG vaccination: a case report - Haydar Ali Tajuddin, Amalina; Siah, Guan Jin; Abdul Wahab, Norasyikin; Mustafa, Norlaila; Sukor, Norlela; Kamaruddin, Norazmi (2018)
Introduction Bacillus Calmette-Guerin (BCG) vaccinations reverse disease by restoring insulin secretion in a rodent model of type 1 diabetes. It stimulates innate immunity by inducing the host to produce tumor necrosis factor (TNF), which, in turn, kills disease-causing autoimmune cells and restores pancreatic beta-cell function through regeneration.